Exact Solutions For Fractional Differential Equations Arising in the Teaching of Mathematical Physical Equations By The Improved (G’/G) Method - Zheng, Bin; Feng, Qinghua (IJRDO- Journal of Educational Research, 2018)
In this paper, we are concerned with seeking exact solutions for space-time fractional differential equations arising in the teaching of the college course mathematical physical equations. The improved (G’/G) method is extended to seek exact solutions for fractional differential equations in the sense of the conformable fractional derivative. Based on a fractional complex transformation, a certain fractional differential equation can be converted into another ordinary differential equation of integer order, and then can be solved subsequently based on the homogeneous balance principle. As for applications of this method, we apply it to solve the (2+1)-dimensional space-time fractional Nizhnik-Novikov-Veselov System, and as a result, construct some new exact solutions for it.